Do Radiologists Report the TNM Staging in Radiology Reports for Head and Neck Cancers? A National Survey Study - Ko, B.; Parvathaneni, U.; Hudgins, P.A.; Anzai, Y. (American Journal of Neuroradiology, 2016)
BACKGROUND AND PURPOSE: CT and MR imaging are widely used for the staging of head and neck cancer. Currently, there are no data regarding whether the primary tumor, nodes, metastasis (TNM) staging is routinely incorporated into radiology reports. We conducted a national survey to determine whether radiologists routinely address staging, in particular regarding T (primary tumor) and N (nodal).MATERIALS AND METHODS: The survey was sent to 782 members of the American Society of Head and Neck Radiology. The survey asked whether they assign TN staging in reports. If they do assign TN staging, what are the reasons for doing so, and if not, what are the barriers or reasons for not including it in the radiology report? The method of measuring the size of the primary tumor and pathologic lymph nodes was also queried.RESULTS: A total of 229 responses were returned (29.3% response rate). Approximately half (49%; 95% confidence interval, 43.55–54.5%) of the responders thought that incorporating TN staging is important. However, only 24.5% (95% confidence interval, 19.8%–29.2%) stated that they routinely assigned TN staging in their radiology reports. The most common barriers were being afraid of being inaccurate (59%) and being unable to remember the staging classifications (58.2%); 76.9% indicated that they measure a primary tumor in 3D.CONCLUSIONS: Staging head and neck cancer based on imaging presents unique challenges. Nearly half of the responding radiologists think it is important to incorporate TN staging in radiology reports, though only a quarter of them routinely do so in practice.H&Nhead and neckTNM(primary) tumor, nodes, metastasis